History and Diagnostic Significance of C-Peptide. (25th May 2008) - Brandenburg, Dietrich
Abstract : Starting with the epoch-making discovery of proinsulin, C-peptide has played an important interdisciplinary role, both as part of the single-chain precursor molecule and as an individual entity. In the pioneering years, fundamental systematic experiments unravelled new biochemical mechanisms and chemical structures. After the first detection of C-peptide in human serum, it quickly became a most useful independent indicator of insulin biosynthesis and secretion, finding application in a rapidly growing number of clinical investigations. A prerequisite was the development of specific immuno assays for proinsulin and C-peptide. Further milestones were: the chemical synthesis of several C-peptides and the accomplishments in the synthesis of proinsulin; the detection of preproinsulin with its bearings on understanding protein biosynthesis; the pioneering role of insulin, proinsulin, C-peptide, and mini-C-peptides in the development of recombinant DNA technology; and the discovery of the enzymes for the endoproteolytic processing of proinsulin into insulin and C-peptide, completing the pathway of biosynthesis. Today, C-peptide continues to serve as a special diagnostic tool in Diabetology and related fields. Thus, its passive role is well established. Evidence for its active role in physiology and pathophysiology is more recent and is subject of the following contributions.